Alpha‐1 Acid Glycoprotein Reduces Hepatic Leukocyte Recruitment in Murine Models of Either Early Endotoxemia or Early Sepsis. (January 2014) - McCurdy, Teresa R.; Patrick, Amanda L.; Eltringham‐Smith, Louise J.; Bhakta, Varsha; Sheffield, William P.; Fox‐Robichaud, Alison E.
Abstract Objective To characterize the effect of systemically administered AGP on early leukocyte recruitment in the livers of endotoxemic or septic mice and to determine whether this is influenced by LPS sequestration. Methods Endotoxemia was induced in C57Bl/6 mice via intraperitoneal injection of LPS. Sepsis was induced in mice by cecal ligation and perforation. AGP (165 mg/kg) or saline (20 mL/kg) or HAS (200 mg/kg) was administered immediately after surgery or LPS injection and the hepatic microcirculation was examined by intravital microscopy at four hour. Results Leukocyte adhesion in the PSV was reduced by treatment with AGP in mice subjected to either LPS or CLP protocols compared to either saline or HAS treatment. AGP‐treated mice also had significantly higher sinusoidal flow in both models. Pre‐incubation of LPS with AGP reduced the ability of LPS to recruit leukocytes to the liver microcirculation. Conclusions AGP was more effective in limiting hepatic inflammation and maintaining perfusion than saline or HAS, in both endotoxemic and septic mice. AGP sequestration of LPS may contribute to its anti‐inflammatory effects.